'Snowstorm', a New Forage Kochia Cultivar with Improved Stature, Productivity, and Nutritional Content for Enhanced Fall and Winter Grazing. Issue 2 (4th March 2013) - Waldron, Blair L.; Larson, Steven R.; Peel, Michael D.; Jensen, Kevin B.; Mukimov, Tolib C.; Rabbimov, Abdulla; ZoBell, Dale R.; Wang, Richard C.; Smith, Rob C.; Deane Harrison, R.; Davenport, Burke W.
Abstract : 'Snowstorm' (Reg. No. CV‐8, PI 666938) forage kochia [ Bassia prostrata (L.) A.J. Scott; syn. Kochia prostrata (L.) Schrad.] was released on 22 Mar. 2012 by the USDA‐ARS and the Utah Agricultural Experiment Station. Snowstorm was evaluated as OTVSEL and Otavny‐select and was developed as a synthetic cultivar using two cycles of recurrent selection for stature, forage production, and adaptation to semiarid environments. Snowstorm was compared with the standard forage kochia cultivar, Immigrant, and other ARS experimental forage kochia populations. Research has shown that Immigrant can increase rangeland productivity three‐ to sixfold and provides critical protein (>70 g kg −1 ) during the fall and winter for livestock and wildlife; however, Immigrant is easily covered by snow because of its short stature. In field comparisons with Immigrant, Snowstorm was similar to Immigrant in establishment and adaptation on semiarid rangelands but was 64% taller (77 versus 47 cm), produced 68% more forage (2526 versus 1504 kg ha −1 ), and had a 22% higher protein content (79 versus 65 g kg −1 ) and 4% higher digestibility (674 versus 648 g kg −1 ) ( P ≤ 0.05). Furthermore, DNA fingerprinting showed that Snowstorm, Immigrant, and experimental populations were genetically unique and distinct from each other. Snowstorm is named for its ability to extend the grazing season into the fall and winter and because it provides ranchers and land managers a new, taller, more productive, more nutritious forage kochia cultivar capable of increasing carrying capacity and nutritional content of fall and winter grazinglands, including locations where snow cover had limited forage kochia use in the past.